2019
DOI: 10.1093/ecco-jcc/jjz117
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Molecular Mediators of Inflammation Differentiate Between Crohn’s Disease and Ulcerative Colitis, Implicating Threshold Levels of IL-10 and Relative Ratios of Pro-inflammatory Cytokines in Therapy

Abstract: Background and AimsFaecal diversion is associated with improvements in Crohn’s disease but not ulcerative colitis, indicating that differing mechanisms mediate the diseases. This study aimed to investigate levels of systemic mediators of inflammation, including fibrocytes and cytokines, [1] in patients with Crohn’s disease and ulcerative colitis preoperatively compared with healthy controls and [2] in patients with Crohn’s disease and ulcerative colitis prior to and following faecal diversion.MethodsBlood samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 76 publications
5
23
0
Order By: Relevance
“…More specifically, in light of preferential deposition of adipose tissue in hips and upper thighs of patients with CD, it is reasonable to argue that fat wrapping of inflamed intestinal tissue in the abdominal area deserves even greater attention than is currently focused. While mesenteric fat has been recognised as a potential barrier to inflammatory markers, to mitigate bacterial transposition and a reservoir of inflammatory adipokines 29 , 36 , we suggest tentatively that this juxtaposition of organ-specific and regional adiposity represents a rationale to refer to Crohn’s disease as a non-alcoholic fatty intestine condition, albeit that our data represent early insights limited to pilot-scale.…”
Section: Discussionmentioning
confidence: 73%
“…More specifically, in light of preferential deposition of adipose tissue in hips and upper thighs of patients with CD, it is reasonable to argue that fat wrapping of inflamed intestinal tissue in the abdominal area deserves even greater attention than is currently focused. While mesenteric fat has been recognised as a potential barrier to inflammatory markers, to mitigate bacterial transposition and a reservoir of inflammatory adipokines 29 , 36 , we suggest tentatively that this juxtaposition of organ-specific and regional adiposity represents a rationale to refer to Crohn’s disease as a non-alcoholic fatty intestine condition, albeit that our data represent early insights limited to pilot-scale.…”
Section: Discussionmentioning
confidence: 73%
“…The impaired epithelial barrier has been associated with inflammatory pathological conditions of the gut and restoration of intestinal function has been proposed as a potential therapeutic target to promote recovery of intestinal homeostasis [ 51 ]. Recently, a microbial anti-inflammatory molecule (MAM) produced by F. prausnitzii efficiently re-established the intestinal barrier structure via the regulation of the tight junction pathway and ZO-1 expression [ 52 ], while previous studies also showed that F. prausnitzii is associated with anti-inflammatory effects via IL10 induction in dendritic cells [ 53 ]. Roseburia intestinalis and bifidobacteria have also been described as effective commensals in promoting intestinal barrier function [ 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result possibly explains the inflammation scores and decreased histological features of the NFXi group. Notably, IL-10 is an influential interleukin that can modulate pro-and anti-inflammatory cytokines 38 , and IL-10 can also suppress exacerbated mucosal immune responses, maintain intestinal homeostasis and tolerance to commensal microbiota 39 and inhibit collagen deposition in the host intestine 30 .…”
Section: Discussionmentioning
confidence: 99%